2018
DOI: 10.3233/jin-180090
|View full text |Cite
|
Sign up to set email alerts
|

Cortical, subcortical and brain stem connections of the cerebellum via the superior and middle cerebellar peduncle in the rat

Abstract: The role of cerebellum in coordination of somatic motor activity has been studied in detailed in various species. However, experimental and clinical studies have shown the involvement of the cerebellum with various visceral and cognitive functions via its vast connections with the central nervous system. The present study aims to define the cortical and subcortical and brain stem connections of the cerebellum via the superior (SCP) and middle (MCP) cerebellar peduncle using biotinylated dextran amine (BDA) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…However, collective data regarding the dento-thalamic connections is rather sparse. The majority published connections highly correspond (VPM, VPL, VL, Po, IL, PF, and VM) with our results (Aumann et al, 1994;Bentivoglio and Kuypers, 1982;Bernard et al, 2013;Cavdar et al, 2018;Faull and Carman, 1978;Middleton and Strick, 1997). Gornati et al (2018) reported that in vitro electrophysiological recordings revealed that optogenetic dentate nucleus stimulation resulted in enhanced charge transfer and action potential firing in VL neurons compared with VM or CL neurons.…”
Section: Discussionsupporting
confidence: 87%
“…However, collective data regarding the dento-thalamic connections is rather sparse. The majority published connections highly correspond (VPM, VPL, VL, Po, IL, PF, and VM) with our results (Aumann et al, 1994;Bentivoglio and Kuypers, 1982;Bernard et al, 2013;Cavdar et al, 2018;Faull and Carman, 1978;Middleton and Strick, 1997). Gornati et al (2018) reported that in vitro electrophysiological recordings revealed that optogenetic dentate nucleus stimulation resulted in enhanced charge transfer and action potential firing in VL neurons compared with VM or CL neurons.…”
Section: Discussionsupporting
confidence: 87%
“…Both parts receive input from all cerebellar nuclei, although the magnocellular portion receives mainly input from the interposed nucleus [11,65,67,77,95,110,111,[217][218][219][220][221][222][223][224], and the parvocellular part predominantly from the dentate nucleus [65,79,110,111,117,218,220,221,225]. Other studies confirm these cerebello-rubral projections, although they do not take the subdivisions into account [32,34,48,54,55,64,83,85,93,105,121,217,[226][227][228][229][230][231][232][233][234][235][236][237]…”
Section: Red Nucleus (Rn)mentioning
confidence: 98%
“…These areas contain a large proportion of serotonergic neurons and are involved in many functions such as emotion, response to stress, reward, regulation of appetite, movement, sexual behavior, sleep, respiration, and pain perception [59,[61][62][63]. The obscurus and magnus nuclei, but not the pallidus nucleus, receive input from the cerebellum, with all three cerebellar nuclei contributing to this output [32,34,55,[64][65][66][67][68].…”
Section: Medullary Reticular Formation (Rf)mentioning
confidence: 99%
“…For the change in AD value in the MCP, a previous case report proved that it is a large nerve bundle formed by afferent fibers from the contralateral pontine nuclei and that damage to it can cause tinnitus and hearing loss (Matsuda, Inagawa, & Amano, 1993). Moreover, Çavdar, Özgür, Kuvvet, Bay, and Aydogmus (2018) found in their study that the cerebellum connected the auditory cortices via the MCP, and Feng et al (2018) demonstrated that the cerebellum plays an important role in the dysfunction caused by tinnitus. In addition, Shelton et al (2017) reported that changes in the WM microstructure in the MCP are associated with executive function.…”
Section: Discussionmentioning
confidence: 98%